Resistance and Social Movement for the Rejection of Gold Mining on Mount Tumpang Pitu Banyuwangi - Adi Saputra Andika (EDP Sciences, 2021)
Mount Tumpang Pitu is a national park and protected forest that functions as a buffer area, a source of water absorption and is inhabited by many habitats, as well as other functions as a natural fortress that can withstand the wind, and giant Tsunami in 1994. The benefits of Mount Tumpang Pitu and the surrounding mountains are vital for the local community. In 2005, the local government of Banyuwangi aimed to extend grant gold mining activities for a mining investor. The government's policy that did not involve the public in a participatory manner in granting mining permits, triggered the community to carry out a movement to reject the gold mining activities. The rejection movement is also a response to disaster concerns, and the impacts that has been felt by the people there. This rejection movement fits to the theory of New Social Movement, considering by the characteristics of its movement. However, the Comprehensive Perspective of Social Movement Theory from McAdam et al., proves that this movement is still weak and accordingly difficult to achieve its goals.